Jihadists of North Africa and the Sahel: local politics and rebel groups - Thurston, Alexander (Cambridge University Press, 2020)
Jihadist movements have claimed that they are merely vehicles for the application of God's word, distancing themselves from politics, which they call dirty and manmade. Yet on closer examination, jihadist movements are immersed in politics, negotiating political relationships not just with the forces surrounding them, but also within their own ranks. Drawing on case studies from North Africa and the Sahel - including Algeria, Libya, Mali, Niger, Burkina Faso, and Mauritania - this study examines jihadist movements from the inside, uncovering their activities and internal struggles over the past three decades. Highlighting the calculations that jihadist field commanders and clerics make, Alexander Thurston shows how leaders improvise, both politically and religiously, as they adjust to fast-moving conflicts. Featuring critical analysis of Arabic-language jihadist statements, this book offers unique insights into the inner workings of jihadist organisations and sheds new light on the phenomenon of mass-based jihadist movements and proto-states. -- Back cover